Microemulsions- A Potential carrier for drug delivery - VUSHAKOLA, POORNIMA; SAILAJA A, KRISHNA (Innovare Journal of Life Sciences, 2016)
Microemulsions have attracted much interest over the past years as potential drug delivery systems because of their transparency ease of in preparation and long-term stability. Micro emulsions provide sustained or controlled drug release for different routes of administration including parenteral administration. It shows advantages in the drug delivery like greater absorption of drugs, alteration of the kinetics of the drug release and decreased toxicity are several advantages in the delivery process. In this article the microemulsion preparation techniques and applications were discussed in detail.